Isolated Nocturnal Hypertension in Children - Awazu, Midori (Frontiers in Pediatrics, 2022)
Isolated nocturnal hypertension (INH) is attracting attention because it has been shown to correlate with target organ damage as well as cardiovascular events in adults. INH has also been reported in children especially in those with underlying diseases including chronic kidney disease and some studies reported association with markers of early target organ damage. INH occupies the majority of nocturnal hypertension. On the other hand, masked hypertension is largely attributed to INH. INH is usually diagnosed by ambulatory blood pressure monitoring. Recently, it became possible to monitor sleep blood pressure by an automated home blood pressure device feasible also in children. The epidemiology, methodology and reproducibility, pathophysiology, relation to target organ damage, and treatment of INH in children will be reviewed here along with adult data.